BIOCHEMICAL PROPERTIES OF RECOMBINANT Β-GALACTOSIDASE FROM STREPTOCOCCUS THERMOPHILUS - Baltin , K.K.; Akishev , Zh.D.; Abeldenov , S.K.; Silayev , D.V.; Khassenov , B.B. (Eurasian Journal of Applied Biotechnology, 2017)
Recombinant β-galactosidase from Streptococcus thermophilus was successfully expressed in Escherichia coli, purified, and biochemically characterized. The gene encoding β-galactosidase was amplified from the genomic DNA of St. thermophilus and cloned into the expression vector pET-28c (+). Using the recombinant vector, a BL21 (DE3)/pLacZST strain-producer was obtained with overexpression of the gene. Optimal culture parameters for producing recombinant β-galactosidase were determined. The recombinant β-galactosidase had an activity of 19 units/mg. Biochemical characterization of recombinant β-galactosidase showed that the enzyme had maximum activity at pH 9.0 and temperature of 60°C. Analysis of the kinetics of lactose hydrolysis gave a Michaelis constant Kmof 10.12 ± 2.5 mM and a limiting value of the initial rate of the enzymatic reaction Vmaxof 0.47 ± 0.027 mM/min. The β-galactosidase has been used in experiments that simulate commercial production conditions, to producea glucose-galactose syrup.